The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Phase Equilibria With Supercritical Carbon Dioxide - Application to the Components of a Biocatalytic Process 2022
DOI: 10.5772/intechopen.105485
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluids: Properties and Applications

Abstract: Currently, both humanity and the whole planet are living in a critical time, which leads us to look for more sustainable formulas to interact with the environment. One of the important changes in the design and operation of chemical processes is the search for environmentally friendly technologies. Many industrial processes are carried out under severe conditions or with reactants that involve the use of strong acids, toxic metal catalysts, organic solvents, and processes at high temperatures and/or pressures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Carbon dioxide is the most commonly utilized SCF because of its outstanding safety and affordable price. The most common method for producing LBNPs with SCF involves altering the ambient pressure of supercritical CO 2 (scCO 2 ) ( 106 ). In a nutshell, scCO 2 is utilized as a solvent, and when fed into a high-pressure vessel, the solubilities of solid lipids and medications in scCO 2 are boosted.…”
Section: Lbnp Synthesismentioning
confidence: 99%
“…Carbon dioxide is the most commonly utilized SCF because of its outstanding safety and affordable price. The most common method for producing LBNPs with SCF involves altering the ambient pressure of supercritical CO 2 (scCO 2 ) ( 106 ). In a nutshell, scCO 2 is utilized as a solvent, and when fed into a high-pressure vessel, the solubilities of solid lipids and medications in scCO 2 are boosted.…”
Section: Lbnp Synthesismentioning
confidence: 99%
“…Also, when the reservoir pressure and temperature exceed the critical temperature (31.1 °C) and critical pressure (7.39 MPa) of CO 2 , CO 2 attains a supercritical state within in situ reservoir conditions . Supercritical CO 2 (sc.CO 2 ) has unique physiochemical properties where its density is close to water, viscosity is close to gas, and has a relatively higher diffusion coefficient . Numerous studies have been reported on CO 2 -EOR methods, including continuous gas injection, water-alternating gas (WAG) injection, tapered WAG, carbonated water injection (CWI), CO 2 huff-n-puff, and CO 2 foam flooding. However, there are challenges associated with every CO 2 -EOR project.…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical carbon dioxide (SC-CO 2 ) extraction has been developed for over forty years. The process is applied in research as well as for industrial purposes [ 23 ]. On a large industrial scale, typical applications are the extraction of hop components, decaffeination of tea and coffee, and the separation of lecithin from oil [ 24 ].…”
Section: Introductionmentioning
confidence: 99%